The emergency medical teams initiative in the WHO African region: a review of the development and progress over the past 7 years - Balde, Thierno; Oyugi, Boniface; Mbasha, Jerry-Jonas; Kamara, Rashidatu; Martinez-Monterrey, Lazaro Gilberto; Relan, Pryanka; Lajolo, Camila; Bompangue, Didier; Fortin, Ann; Okeibunor, Joseph; Salio, Flavio; Braka, Fiona; et al. (Frontiers in Public Health, 2024)
The WHO Emergency Medical Teams (EMT) Initiative works to strengthen national surge capacities and, when needed, facilitates the deployment of medical teams to countries and territories during health emergencies.Objective: This paper describes the development and progress of national EMTs in the WHO African Region over the past seven years and elucidates the lessons learned, the complexity and challenges in the process.Methods: This article utilises a retrospective and descriptive analysis of the development of EMTs in the WHO African region over the past seven years. The study is based on document reviews of EMTs' mission reports, assessments, surveys, monthly bulletins and meeting minutes, and key informant interviews (KIIs) (n=5) with the EMT teams' members on shared field experiences. Data analysis was done thematically.The EMT Initiative was launched in the WHO African Region in December 2017 in Senegal. The initial regional sensitisation workshops and country awareness campaigns allowed the countries to implement the initiative, conduct regional and local deployments, and enhance skills and knowledge transfer development. Its implementation necessitated the development of the regional strategy, aligning with the global EMT 2030 strategy that proposed the establishment of national EMTs, the development of the implementation roadmap and a coordination mechanism, and the establishment of a regional training centre. These developments envisioned having every country respond rapidly and effectively to national emergencies, leveraging regional and sub-regional capacities to support vulnerable communities and others in need and strengthening information systems, evidence and research.The EMT initiative is an imperative component that would allow better-targeted management of health emergencies in the region. There is a need to work on additional components, such as a context-specific framework for collaborations and partnerships that would enhance deployment and procurement modalities and the complementarity between other regional initiatives to improve the work.